The preparation of the couple to the Christian marriage: a pastoral-legal overview - INTERGUGLIELMI, ANTONIO (Prawo Kanoniczne, 2017)
This brief analysis is inspired by the words of Pope Francis in his speech addressed to the officials of the Tribunal of the Roman Rota on 22nd January 2016: "a fortiori, pastoral urgency involving all Church structures is leading us toward a shared intention to provide adequate preparation for marriage in a kind of new catechumanate. " In light of the recent reform of the process for the declaration of nullity of marriage, we have studied in deep both the need for a link between the pastoral and judicial praxis - for the purpose of "proper preparation" of engaged couples for marriage - and the new needs that the reality of family demands. So we have seen that from the court cases that the most frequent ones leading to the declaration of matrimonial nullity could be avoided and even forewarned by an effective preparation of engaged couples, with a true journey of rediscovery of the faith. It is also clear from our research as the need for an ongoing tutoring for married couples in the first few years of marriage, is not only in conformity with the norms of the CIC, but for some time emerged in the documents of the Pastoral Family of the Holy See.